The contribution of Potamogeton crispus to the phosphorus budget of an urban shallow lake: Lake Monger, Western Australia - Leoni, B.; Marti, Clelia; Forasacco, E.; Mattavelli, M.; Soler, V.; Fumagalli, P.; Imberger, J.; Rezzonico, S.; Garibaldi, L. (2016)
© 2015, The Japanese Society of Limnology. Lake Monger (Perth, Western Australia) is a highly eutrophic lake, characterised by very low species richness of macrophytes with the dominance of Potamogeton crispus. Mesocosm experiments were performed using water and plants collected from the lake to determine the effects of vegetation decay on the phosphorus (P) con centrations in the overlying waters. After 2 weeks of experimental incubation of mesocosms with and without re-oxygenation, P concentrations in the water column were significantly higher, showing a quite similar effect of P. crispus on the phosphorus release in different mesocosms. The results of our study provide clear evidence that the P concentrations in overlying waters mainly depend upon the plant P content and developmental stage. Although many sources contribute to the nutrient load of Lake Monger, macrophyte harvesting, prior to its senescence, might constitute a significant in-lake measure for reducing the internal P load.